2011
DOI: 10.14411/eje.2011.062
|View full text |Cite
|
Sign up to set email alerts
|

Parasitylenchus sp. (Tylenchomorpha: Allantonematidae) parasitizing field populations of Harmonia axyridis (Coleoptera: Coccinellidae)

Abstract: Abstract. Adults of the invasive harlequin ladybird, Harmonia axyridis (Coleoptera: Coccinellidae), were found to be parasitized by nematodes (Tylenchomorpha: Allantonematidae) in Denmark. The nematodes were identified as Parasitylenchus sp. Major morphological characters of the nematodes did not differ significantly from Parasitylenchus coccinellinae Iperti & van Waerebeke 1968, but minor deviations in egg dimension and tail length were measured. Parasitism was only recorded in early autumn, with prevalence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…No empirical confirmation of this exists so far, but the finding of Sluss (1968) that the successful development of D. coccinellae was prevented in microsporidia-infected ladybirds (Hippodamia convergens Guérin) makes this hypothesis plausible. It should also be tested whether other pathogens and parasites of H. axyridis, especially the nematode Parasitylenchus bifurcatus Poinar and Steenberg (Harding et al 2011;Poinar and Steenberg 2012;Haelewaters et al 2017), can interfere with D. coccinellae larval development.…”
Section: Homalotylus Spp (Hymenoptera: Encyrtidae)mentioning
confidence: 99%
“…No empirical confirmation of this exists so far, but the finding of Sluss (1968) that the successful development of D. coccinellae was prevented in microsporidia-infected ladybirds (Hippodamia convergens Guérin) makes this hypothesis plausible. It should also be tested whether other pathogens and parasites of H. axyridis, especially the nematode Parasitylenchus bifurcatus Poinar and Steenberg (Harding et al 2011;Poinar and Steenberg 2012;Haelewaters et al 2017), can interfere with D. coccinellae larval development.…”
Section: Homalotylus Spp (Hymenoptera: Encyrtidae)mentioning
confidence: 99%
“…The association between Harmonia axyridis and Hesperomyces virescens is an example of the latter, less frequent, process. The case described above can be included with an increasing body of evidence that the invasive populations of the harlequin ladybird are not only susceptible to some native parasites such as H. virescens, the mite Coccipolipus hippodamiae (McDaniel & Morrill) (Rhule et al, 2010;Riddick, 2010) and allantonematid nematodes (Harding et al, 2011;Roy et al, 2011b;Poinar & Steenberg, 2012), but also contribute to their dispersal, increase in prevalence and intensity of infection.…”
Section: Newly Emergent Host-parasite Associationmentioning
confidence: 99%
“…A recently described species, Parasitylenchus bifurcatus Poinar & Steenberg is recorded infecting a Danish population of H. axyridis since 2009(Harding et al, 2011Poinar & Steenberg, 2012) and in 2009 allantonematid nematodes were found infecting H. axyridis in Minnesota (USA) (Roy et al, 2011b). In contrast to ectoparasitic Hesperomyces and Coccipolipus, Allantonematidae are endoparasites.…”
Section: What Makes H Axyridis An Exceptionally Suitable Host?mentioning
confidence: 99%
“…Adult multicolored Asian lady beetles have been found parasitized by nematodes in Denmark in 2009 and the parasitic nematode was subsequently described as a new nematode species Parasitylenchus bifurcatus (Harding et al, 2011, Poinar andSteenberg, 2012). Diagnostic morphological characters of Parasitylenchus bifurcatus are a straight stylet lacking basal thickenings, an excretory pore opening at the level of or somewhat posterior to the nerve ring and a gubernaculum, a narrow bursa in the males and a forked tail tip in the vermiform (infective) females and juvenile males.…”
Section: Introductionmentioning
confidence: 99%
“…Different developmental stages of P. bifurcatus, first generation parasitic females, subsequent generation parasitic females, vermiform (infective) females, males and juvenile nematodes, occurred together in the body cavity of both female and male H. axyridis (Harding et al, 2011, Poinar and Steenberg, 2012, Raak-van den Berg et al, 2014. The prevalence of infected adult ladybirds collected in nature ranged from 2 -47 % and increased up to 60 % when field-collected ladybirds were incubated in the laboratory for 30 days Steenberg, 2012, Haelewaters et al, 2017).…”
Section: Introductionmentioning
confidence: 99%